ANALISIS GELATINISASI TEPUNG MAIZENA PADA PEMBUATAN PASTA FETTUCCINE ANALISIS GELATINISASI TEPUNG MAIZENA PADA PEMBUATAN PASTA FETTUCCINE - Asniwati Zainuddin (Fakultas Pertanian Universitas Ichsan Gorontalo, 2016)
The purpose of this study is to find influence gelatinisasi cornmeal of water levels and speed rehidrasi to making pasta fettuccine and to know proper formulation of wheat flour and cornmeal in making pasta fettuccine. As for treatment since this research is formulation between white flour and cornmeal, : A0: wheat flour 100 %, A1: wheat flour 90 % + cornmeal 10 %, A2: wheat flour 80 % + cornmeal 20 %, A3: wheat flour 70 % + cornmeal 30 %. Data processing with the methods design random complete RAL with twice remedial then the data treated in the analysis fingerprint variety. The research results show influence gelatinisasi to making pasta “fettuccine”. Formulations of white flour and cornmeal is increasing water levels , and lowering rehidrasi resources on pasta “fettuccine”.. The right method to research this is based on the the water level and speed rehidrasi where the treatment 70 % wheat flour + 30 % cornmeal similarly based on the organoleptik covering color , scent , and taste.